In search of the twin transition: The limited performativity of the "green and digital" transitions in the European automotive industry - Juan Sebastian Carbonell (European Commission, Joint Research Centre (JRC), 2024)
This paper examines the concept of " twin transition " using the core/periphery structure of the European automotive industry as a case study. This term has emerged in recent years as a new leitmotif in international organisations and industrial companies. The idea is that the digital and green transitions can fuel each other in a virtuous economic circle of " smart growth ". This paper defends that this concept is part of the automotive industry's long history of socio-technical paradigms. Using the theories on the performativity of economic concepts, we deconstruct the idea of a " twin transition ". We show that it is necessary to dissociate the production process from the output in order to understand the possible interactions between the two transitions. For this, we describe the regional structure of the European automotive industry in terms of core and periphery, we show then the forms taken by digitalisation and electrification in the value chain of the European automotive industry in processes and products. Finally, we show that the concept of " twin transition " has little empirical basis, but rather aims to attract resources in the context of significant economic uncertainty and the lack of coherent industrial policy.
Keywords: 330; twin transition; automotive industry; digitalisation; green transition; electromobility